BENTUK, FUNGSI, DAN MAKNA LUKISAN PADA INTERIOR ALTAR GEREJA ST. ANTONIUS KOTABARU YOGYAKARTA - Nugraheni, Regina Ratih; Budiwiyanto, Joko (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
This research is motivated by Catholics who come to church increasingly do not understand the meaning and message contained in the church building, even though the symbols and everything contained in the church building are made not only as decoration, but every part in the church has meaning. related to Catholic life. One church that has a message framed in the form of a painting in its interior is the Catholic Church of St. Antonius in Kotabaru, Yogyakarta. The paintings on the walls of this church have very interesting forms, functions, and meanings because they are related to the contents of the holy book of the Gospel of John. This study aims to determine the form, function, and meaning of the painting on the interior of the altar of the Catholic Church of St. Antonius Kotabaru, Yogyakarta. The results of the study are as follows, the form of painting on the church wall is a decorative painting. The function of painting is to beautify the interior of the church room, as an identity for the Catholic church that uses elements of regional inculturation in the interior of the room, and as a medium of da'wah in introducing the holy book of the Gospel of John to Christians. The form of the painting has a meaning, that a leader should know the needs of the community, just as Jesus knew the needs of his people.